Präparation einer einzelnen Skelettmuskelzelle - Rüdel, Reinhardt (IWF (Göttingen), 1977)
Präparation einer einzelnen Muskelfaser des M. semitendinosus des Frosches. Prüfung der Kontraktionsfähigkeit der isolierten Muskelfaser mit zwei Reizsonden. Einbringen der Faser in eine Experimentierkammer.

A single fibre from a frog semiteninosus muscle is dissected in a special dissection dish. The main stages of this procedure are as follows: about 2/3 of the fibres are cut off by using fine scissors, the connective tissue in the remaining part of the preparation is made loose by stretching and pulling, the preparation is subdivided in small fibre bundles, one bundle is chosen for final dissection, and the single fibre is isolated from its last fellow fibres. Finally, the isolated fibre is tested for all-or-nothing twitches.
Keywords: Medicine; Muskelzelle; Skelettmuskelzelle; Präparation / Skelettmuskelzelle; muscle contraction; muscle fibre; skeletal muscle fibre; preparation / skeletal muscle fibre